Burden and Determinant of Inadequate Dietary Diversity among Pregnant Women in Ethiopia: A Systematic Review and Meta-Analysis - Hagos Degefa Hidru; Meresa Berwo Mengesha; Yared Hailesilassie; Fissaha Tekulu Welay (Journal of Nutrition and Metabolism)
Background. Inadequate dietary diversity intake during pregnancy results in increased risks of negative maternal and perinatal outcomes. About one million neonates die on the first day of life due to inadequate dietary intake during pregnancy as a result of maternal complication and adverse birth outcomes. This review summarizes the burden of inadequate dietary diversity and its determinants among pregnant women at the national level of Ethiopia. Methods. Studies were retrieved from selected electronic databases, including PubMed, Cochrane Library, and Google Scholar. Random-effects model meta-analysis was used to estimate the pooled burden of inadequate dietary diversity and its determinants at a 95% confidence interval with its respective odds ratio (OR) using statistical R-software version 3.6.1. Moreover, quality appraisal of the included studies, publication bias, and level of heterogeneity were checked with subgroup analysis and sensitivity influential test. The searches were restricted to articles published in the English language only, and Medical Subject Headings (MeSH terms) was used to help expand the search in advanced PubMed search. Result. A total of 850 articles were identified through the initial search of which 21 studies were included in the final review yielding a total sample size of 9,230 pregnant women. The pooled prevalence of inadequate dietary diversity was 53% (95% CI: 44%, 62%). Food insecurity [AOR = 2.18, (95% CI: 1.02, 4.63)], family size of greater than four [AOR = 1.46, (95% CI: 1.10, 1.95)], rural residence [AOR = 4.52, (95% CI: 1.02, 20.09)], no formal educational status [AOR = 4.50, (95% CI: 1.02, 20.09)], and a lack of counseling about dietary diversity [AOR = 2.75, (95% CI: 2.17, 3.48)] were among the significantly associated factors for inadequate dietary diversity. Conclusion. In this review, there was a high prevalence of inadequate dietary diversity among pregnant women at the national level in Ethiopia. Therefore, strengthening early counseling and diagnosis of dietary intake and undernutrition during the antenatal care period is important.